ESENSI PERLINDUNGAN HAK CIPTA ATAS KARAKTER FIKTIF - Michael Hans (Universitas Islam Darul Ulum, 2018)
Fictional works in the media of cinematography, literature, drama, novel, comic, as well as video game often produce fictional characters that become the foundation of those works in which such characters are important components that are employed by the creators or authors to support the theme and conflict. Characters are also useful to develop the theme so that the creators’ or authors’ message can be clearly delivered. With a good character, readers or audiences may comprehend the story better and it is often the fictional characters are portrayed in those media that drive and control the story. Fictional characters can also be a valuable asset for the creators or the Copyright holders considering the economic and moral value in those characters. The objectives of this research is to find the essence of copyright protection for fictional characters.